ADOPTION OF ARTIFICIAL INTELLIGENCE IN RECRUITMENT: OPPORTUNITIES, RISKS, AND ETHICAL CHALLENGES - Dewi Damayanti; Oktavianti Oktavianti; Rizki Eka Putra Eka Putra (RADJA PUBLIKA, 2025)
This article examines the dual-impact of integrating Artificial Intelligence (AI) into organizational recruitment processes. It highlights the significant advantages, including enhanced efficiency through automation, improved hiring quality via predictive analytics, and a more responsive candidate experience. Conversely, the analysis identifies critical risks such as algorithmic bias, lack of decision-making transparency, and substantial data privacy concerns. The paper argues that realizing the benefits of AI while mitigating its perils necessitates a strategic, hybrid approach. It concludes that sustainable success depends on a synergistic model where technology is guided by robust ethical frameworks and continuous human oversight, ensuring recruitment is not only more efficient but also equitable and trustworthy.